2011
DOI: 10.4269/ajtmh.2011.10-0015
|View full text |Cite
|
Sign up to set email alerts
|

Chagas Disease: Increased Parasitemia during Pregnancy Detected by Hemoculture

Abstract: Abstract. One hundred fifty-two Trypanosoma cruzi seropositive women were submitted to a single hemoculture; 101 were pregnant, and 51 were not pregnant. Seven tubes from each individual were harvested with liver infusion tryptose (LIT) medium and observed monthly until the fifth month. Hemocultures were positive in 50% (76 of 152) of the women. Results showed that the positivity was 29.4% (15 of 51) among non-pregnant women and 60.4% (61 of 101) in pregnant women ( P < 0.05). In relation to gestational age, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 12 publications
2
16
0
1
Order By: Relevance
“…This is in line with previous reports in chronically infected pregnant women displaying higher parasitemia than non-pregnant ones [60]–[64]. This limited effect on chronic parasitemias might be associated with some degree of gestation-associated immune depression (imbalance of types 1 and 2 immune responses and increased amounts of Treg cells; [62], [65]), probably insufficient enough to modify significantly the high parasite levels produced in acute infection.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous reports in chronically infected pregnant women displaying higher parasitemia than non-pregnant ones [60]–[64]. This limited effect on chronic parasitemias might be associated with some degree of gestation-associated immune depression (imbalance of types 1 and 2 immune responses and increased amounts of Treg cells; [62], [65]), probably insufficient enough to modify significantly the high parasite levels produced in acute infection.…”
Section: Discussionsupporting
confidence: 92%
“…The primary drawback associated with parasite isolation is selection bias for particular subpopulations, initially by preferential outgrowth due to faster dividing rates and/or culture media [55,119,120] and subsequently by loss of clonal diversity from serial maintenance in axenic culture or animals [121–126] . Hemoculturing is laborious; recovery rates are usually less than 30% among chronic patients [127] and almost entirely determined by parasite load and distribution within the starting sample. Xenodiagnosis, which can facilitate greater parasite recovery, has also been shown to vary depending on vector permissibility to local strains [128–130] .…”
Section: T Cruzi Clinical Genotyping: Perils and Pitfallsmentioning
confidence: 99%
“…Congenital transmission of T . cruzi is suggested to occur when the phagocytic capacity of the placenta is compromised [ 43 ] and a significant amount of blood parasites are present in the infected women [ 44 ]. Others have suggested that the maternal-fetal transmission of T .…”
Section: Discussionmentioning
confidence: 99%